2014
DOI: 10.1136/tobaccocontrol-2013-051512
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and determinants of electronic cigarette use among Finnish adolescents in 2013: a population-based study

Abstract: BackgroundA wide range of electronic cigarettes (e-cigarettes) are now on the market. We studied e-cigarette awareness and use, determinants and sources of e-cigarettes, the e-liquids used in them and exposure to e-cigarette advertisements among adolescents in Finland. Among smokers, we studied the association of e-cigarette use and interest in smoking cessation.MethodData were obtained from a national survey of 12–18-year-old Finnish adolescents in 2013 (N=3535, response rate 38%). Descriptive statistics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
118
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(146 citation statements)
references
References 23 publications
23
118
1
4
Order By: Relevance
“…Nicotine-free cartridges were less popular than nicotine-containing cartridges among both groups. This is in line with previous studies, and illustrates the importance of nicotine as an ingredient of the product and e-cigarette users' addiction to nicotine 8,16,17,49,50 . The two most commonly mentioned reasons for using e-cigarettes were that the product was considered as less detrimental for one's health and served as a smoking cessation tool.…”
Section: Discussionsupporting
confidence: 78%
“…Nicotine-free cartridges were less popular than nicotine-containing cartridges among both groups. This is in line with previous studies, and illustrates the importance of nicotine as an ingredient of the product and e-cigarette users' addiction to nicotine 8,16,17,49,50 . The two most commonly mentioned reasons for using e-cigarettes were that the product was considered as less detrimental for one's health and served as a smoking cessation tool.…”
Section: Discussionsupporting
confidence: 78%
“…11 The Centers for Disease Control reported that, during 2011-2012, use of e-cigarettes increased from 3.3% to 6.8% among students in grades 6-12. 12 Similar increases 13 and high levels of ever use 14 have also been observed in other countries where e-cigarettes are being marketed (e.g., in Korea and Finland). In light of the rapid growth of the e-cigarette industry, the lack of consistent local and federal policies around the use and marketing of these products, and the potential for e-cigarette use to promote the uptake of traditional tobacco products and nicotine addiction, it is imperative to monitor and understand e-cigarette use behaviors among adolescents.…”
Section: E-cigarette Use Among High School and Middle School Adolescesupporting
confidence: 57%
“…Similarly, in Connecticut, current cigarette smokers were most likely to consistently use nicotine e-cigarettes (59.2%), followed by ever smokers (31.9%) and never-smokers (11.4%) 18 . An exception is found in the Finnish data, where 65.7% of adolescent ever e-cigarette users had used nicotine e-cigarettes 17 . However, this sample had a low rate (8.3%) of tobacco never smokers, which suggests that a number of those using nicotine e-cigarettes may have previously used tobacco.…”
Section: Regular Use Of E-cigarettesmentioning
confidence: 85%
“…Seven studies [15][16][17][18][19][20][21] reported on the awareness of e-cigarettes among adolescents. Awareness of e-cigarettes was reported at 50.3%, 77.3% and 90.1% in the US 15 18 19 .…”
Section: Awareness Of E-cigarettesmentioning
confidence: 99%